Design of rural bioclimatic house for cold humid andean weather: Facatativá- Colombia case study - Sánchez Amaya, Cesar Andres (2021)
The following document aims at deploying rural productive housing models based on bioclimatic design items focalized on cold humid Andean weather, and starting from the analysis of traditional dwelling in the area. The case study is located in Facatativá, a town in Cundinamarca, which is a region with diverse climatic features due to its strong wind, temperature variations from 0° Celsius during the day until 20° Celsius at late night with frost seasons in the early morning, and a high relative humidity. On top of that, precipitations are quite high over the year. As a tradition, rural dwelling has characteristics of compact buildings with proper local elements like pedestrian corridors around the house as well as the porch, among others. These features of climate, as well as the mentioned architectural typology factors of the analyzed house prototypes, generate thermal discomfort on habitat units in a big time period of the year, raising energy consumption to obtain thermal gain. Through these housing models, the main goal is to propose passive energy strategies for rural households, enhancing comfort levels on houses´ interior; developing a base guideline for future rural dwelling design and building in the case study area, and therefore helping to nurture people´s life quality and reduce energy consumption regarding building environment and home´s operability